Computer Lab Timetabling Using Genetic Algorithm Case Study - Unit ICT - Abdullah, Amran (2006)
Genetic Algorithm is one of the most popular optimization solutions used in various applications such as scheduling. The flows of GA are using selection, crossover and mutation operators applied to populations of chromosomes. This paper reports the techniques using GA in scheduling. Class timetabling problem is one of the applications in scheduling. Basically, it will look into matters such as putting students into certain time slot. These aspects are important for lab session to avoid clash and no students can sit more than one lab session in a same time slot. The other constraint is the student workload should be arranged less than three session in a row. The computer lab timetabling problem at Unit ICT, Fakulti Teknologi Maklumat, Universiti Utara Malaysia is introduced and the prototype has been developed using Java language. The prototype suggested several feasible solutions to the user.